2020
DOI: 10.1101/2020.07.10.197541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved characterisation of clinical text through ontology-based vocabulary expansion

Abstract: Background: Biomedical ontologies contain a wealth of metadata that constitutes a fundamental infrastructural resource for text mining. For several reasons, redundancies exist in the ontology ecosystem, which lead to the same concepts being described by several terms in the same or similar contexts across several ontologies. While these terms describe the same concepts, they contain different sets of complementary metadata. Linking these definitions to make use of their combined metadata could lead to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For example, the current measure of information content is weighted by the frequency the concept appears in the corpus, however these can also be calculated topologically, on the basis of how general or specific the classes are [24]. Our previous work has also demonstrated that expansion of vocabulary [25] and ontology extension [26] can improve performance of a similar tasks. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [27], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [28].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the current measure of information content is weighted by the frequency the concept appears in the corpus, however these can also be calculated topologically, on the basis of how general or specific the classes are [24]. Our previous work has also demonstrated that expansion of vocabulary [25] and ontology extension [26] can improve performance of a similar tasks. Recent work has also explored alternative methods for employing ontology axioms and taxonomy for classification and ranking problems, such as the conversion of ontology axioms to vectors [27], an approach which has been demonstrated to improve performance when compared semantic similarity approaches [28].…”
Section: Resultsmentioning
confidence: 99%
“…Both the construction of the ontology, and thereby analysis performance could be affected by investigating the use of other Komenti features, particularly those for negation detection and synonym expansion [25, 26]. In the former case, the evaluation of negation could prevent incorrect or explicitly negated facts from being used in the produced knowledgebase, while the latter case has been shown to improve overall characterisation of text.…”
Section: Discussionmentioning
confidence: 99%
“…Komenti also includes a novel vocabulary expansion algorithm, adding additional labels and synonyms for terms that can be matched in text, by linking equivalent classes between ontologies using lexical and semantic queries. This has provisionally been shown to vastly increase the scale of vocabulary available in several ontologies, the amount of information returned in information retrieval tasks, and to improve the performance of semantic analysis of clinical text [8].…”
Section: Approachmentioning
confidence: 99%
“…Since Komenti outputs annotations in a simple tabular format, analysis software can easily make use of the produced information. In a previous experiment, labels derived by Komenti from clinical text were used in semantic similarity analyses [8]. Komenti also provides several features for internal analyses of its annotations.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation